KOMUNIKASI RITUAL GAREBEG DI KERATON YOGYAKARTA - Yohanes Arie Kuncoro (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
This research reviewed ritual communication in Garebeg ceremony in Yogyakarta Palace. The Garebeg ceremonies were being held in Muslim celebrations such as of Eid al- Fitr (Garebeg Shawwal), Eid al- Adha (Garebeg large), Maulud Prophet (Garebeg Mulud). Garebeg ceremonies identically with Paredes (Gunungan), which means Yogyakarta Palace keeps the tradition and the ancestors cultural by providing Paredes to communities. This Research uses Constructivist Paradigm and Ethnographic Communication method, especially method of Speaking by Dell Hymes. The purpose of this study to determine the value of norms, attitudes and belief system of the people in the Yogyakarta Palace on Garebeg ceremony. The ritual of Javanese culture, as well as the nature and meaning of communication rituals in ceremonies Garebeg, also know the variety of communication in Garebeg ceremony. The results are seven communication phenomenon such as Tumplak Wajik, Yasa Paredes, Gladen, Garebeg Paredes, Ngabekten, Sekaten and Garebeg Mulud Dal. This research’s contributions are three communication pattern which is hijab Salem, tanda yekti and syiar Islam. This research contributes to give insight about communication patterns and ritual processions in Garebeg ceremony.